2022
DOI: 10.3390/ijms23158789
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Associations in Delayed Cerebral Ischemia after Aneurysmal Subarachnoid Hemorrhage

Abstract: The prognosis for patients with aneurysmal subarachnoid hemorrhage (aSAH) is heavily influenced by the development of delayed cerebral ischemia (DCI), but the adequate and effective therapy of DCI to this day has not been resolved. Multiplex serum biomarker studies may help to understand the pathophysiological processes underlying DCI. Samples were collected from patients with aSAH at two time points: (1) 24 h (Day 1) and (2) 5–7 days after ictus. Serum concentrations of eotaxin, FGF-2, FLT-3L, CX3CL1, Il-1b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Few observational studies had been conducted to investigate the relationship between FGFs and IA, most of which focused on FGF-2 (also known as bFGF). It was reported that higher expression level of FGF-2 was associated with IA and might contribute to vascular remodeling [31], while contradictory nding revealed that the expression pattern of FGF-2 did not differ in normal arterial, ruptured aneurysm, or unruptured aneurysm wall [32,33]. Evidence provided by in vitro and in vivo experimental studies showed that cellular proliferation, tissue brosis, and vascular wall thickness were enhanced by FGF-2 in aneurysm models [34,35].…”
Section: Discussionmentioning
confidence: 98%
“…Few observational studies had been conducted to investigate the relationship between FGFs and IA, most of which focused on FGF-2 (also known as bFGF). It was reported that higher expression level of FGF-2 was associated with IA and might contribute to vascular remodeling [31], while contradictory nding revealed that the expression pattern of FGF-2 did not differ in normal arterial, ruptured aneurysm, or unruptured aneurysm wall [32,33]. Evidence provided by in vitro and in vivo experimental studies showed that cellular proliferation, tissue brosis, and vascular wall thickness were enhanced by FGF-2 in aneurysm models [34,35].…”
Section: Discussionmentioning
confidence: 98%
“…Few observational studies had been conducted to investigate the relationship between FGFs and IA, most of which focused on FGF-2 (also known as bFGF). It was reported that higher expression level of FGF-2 was associated with IA and might contribute to vascular remodeling [ 32 ], while contradictory finding revealed that the expression pattern of FGF-2 did not differ in normal arterial, ruptured aneurysm, or unruptured aneurysm wall [ 33 , 34 ]. Evidence provided by in vitro and in vivo experimental studies showed that cellular proliferation, tissue fibrosis, and vascular wall thickness were enhanced by FGF-2 in aneurysm models [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spantler et al ( 43 ) analyzed a multiplex serum biomarker in 112 patients with aSAH at two time points. Their findings illustrated that monocyte chemotactic protein-3 and chemokine (C-X3-C motif) ligand-1 concentrations at Day 5–7 were relevant to DCI after aSAH.…”
Section: Application Of Peripheral Blood Biomarkers In Ruptured Intra...mentioning
confidence: 99%